Social inclusion-based library development strategies in agricultural institutions - Junaidi, Herwan; Muljono, Pudji; Syaukat, Yusman (Universitas Padjadjaran, 2025)
Social inclusion-based library transformation is a library service dedicated to improving the community's quality of life and welfare through literacy. The implementation of this program targets the community, farmers, extension workers, and stakeholders in West Java. This research analyzed internal and external factors that influenced the development of libraries based on social inclusion in supporting regional development. This study used a qualitative analysis approach through observation and interview methods with seven respondents involved in social inclusion-based libraries. The study results indicated that the development of social inclusion-based libraries held great potential to improve the community quality of life and support regional development through literacy. The most influential internal and external factors included increased cooperation with village governments and related agencies, strengthening the capacity of human resources for library management, promotional programs, and reinforced institutions and regulations. The SWOT-AHP analysis prioritizes future program development strategies for the institutional model of social inclusion-based libraries, with a focus on encouraging the active role of farmer groups and promoting increased cooperation with related ministries/institutions and boosting increased cooperation with village governments. These three strategies are considered the most effective in strengthening the impact of social inclusion-based library programs on community development, especially in the agricultural and rural sectors.